Comparative study of the prevalence of depression between the XI and XII class students of medical stream from urban schools of Punjab - Gill, Gurshan S.; S., Avneet; Goyal, Sandeep K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescence is considered a stressful period due to physical, psychological, sexual changes and is also influenced by maturity. Purpose of this study was to compare the prevalence of depression among XIth and XIIth class students of medical stream in urban schools of Ludhiana, Punjab. Methods: Present study was Cross-sectional study, conducted in in students, studying in urban schools of Jamalpur area of Ludhiana city. The investigator personally visited all the seven schools and went to both the class XI and XII and administered the study tool to each student of medical stream. Results: 253 students from medical stream of 11th and 12th class were considered for present study. Almost equal number of students in medical stream were studying in class XI and class XII, with slight over-representation (52.9%) of students in class XI. Majority (71.1%) of the students were females, and about half of the total students were of 16 years of age. Out of total students 84.6% students were suffering from depression with 17.8% having severe depression. Out of 134 students in Class XIth 81.3% had depression while 88.2% of 119 students in class XIIth were depressed, difference was not statistically significant. As the age increases the severity of depression in students also increases. At 15 years of age students suffering from moderate to severe depression is 31% whereas at 18 years of age 57% students were suffering from moderate to severe type of depression. There was a significant difference of prevalence of depression in between males and females, with females (89.4%) outnumbering males (72.6%). Conclusions: The overall prevalence of depression in our study was 84.6% and it is a prudent reminder of the extreme pressure the adolescent face in this particular age. Compared to other studies the percentage is alarmingly high.